ASPEK EKONOMI IMPLEMENTASI ”GREEN PORT” PADA PELABUHAN INDONESIA (SEBUAH KAJIAN LITERATUR) - Maulita; Fabiola B Luturmas; Rahmat, (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
Ports are an important part of the economy of a country and region. In addition to having a positive impact on the economy, the port also has an impact on the environment, based on awareness of environmental sustainability, the government issued regulations regarding Green Port. Green Port can be seen from 3 aspects, namely environmental, economic and social. This research aims to see the impact of Green Port implementation from the economic aspect. This research uses a literature review of several journals that discuss Green Port implementation. The results of this study found that the impact of Green Port implementation from the economic aspect at the beginning of the implementation there will be costs that must be borne by the Port in the form of initial investment, but in the future it will provide benefits for the port such as port operational efficiency and increase profitability.